Phenomenon of Average Stock Returns of LQ45 Index Companies in 2017-2022 - Putri, Vikka; Setyawan, Ignatius (Politeknik Negeri Madiun, 2024)
The study aims to determine the effect of stock beta and financial performance on stock returns by using stock beta, current ratio (CR), debt to equity ratio (DER), price to book value (PBV), net profit margin (NPM) as measuring instruments for the dependent variable and using stock return as measuring instrument for the independent variable. The sample population of the study was 32 companies in the LQ45 Index for the period 2017-2022. Purposive sampling is the sampling technique for this study. The results of the study found that there were differences in research results before and during the Covid-19 pandemic. Before the Covid-19 pandemic, stock beta, current ratio (CR), price to book value (PBV), Net Profit Margin (NPM) had a significant positive effect on stock returns and debt to equity ratio (DER) had a significant negative effect on stock returns. During the Covid-19 pandemic, stock beta, current ratio (CR), price to book value (PBV), net profit margin (NPM) had a significant negative effect on stock returns and debt to equity ratio (DER) had a significant positive effect on stock returns.